Analisis Manajemen Strategi dan Pengembangan Olshop Siti Munira dengan Pendekatan Ansoff Matrix - Yulia, Safina (Teewan Journal Solutions, 2025)
This study aims to analyze the management strategy applied to Olshop Siti Munira using the Ansoff Matrix approach. In facing increasingly tight competition in the e-commerce market, it is important for olshop businesses to formulate strategies that can strengthen their position in the existing market and identify opportunities for sustainable growth. This study uses a qualitative descriptive approach by collecting primary data in the form of interviews and observations of managers and observations of Olshop Siti Munira's business performance in the last few months. The results of the study indicate that Olshop Siti Munira is currently in the Market Penetration quadrant in the Ansoff Matrix, which focuses on increasing market share with existing products. Despite fluctuations in monthly turnover, the company managed to maintain stable income by increasing promotions and maintaining product quality. This study also identified that in order to continue to grow, Olshop Siti Munira needs to consider product development and market development strategies, such as introducing new products and expanding reach to new areas. Overall, the application of the Ansoff Matrix theory helps Olshop Siti Munira to formulate more structured strategic steps to increase competitiveness and ensure sustainable business growth. Therefore, this study contributes to the understanding of effective business strategies in managing online shops in a very dynamic market.